Cooperativa Escolar Coopersete: desenvolvimento individual e coletivo dos estudantes a partir de seu envolvimento com a proposta da cooperativa escolar - Strohm, Iria Liane (Universidade do Vale do Rio dos Sinos, 2020)
The present article focus on analyze the development of individual and collective students who participate in a cooperative school from their environmental wich the cooperative's proposal is the procedures necessary to establish cooperative schools and the influence of this experience prepararing the personal and professional life of their members . The research took place on Cooperativa Escolar CooperSete in the city of Caxias do Sul / RS, through structured interviews. The development of the article took place at a very particular moment in our lives in all aspects, we find ourselves between of a global pandemic, social isolation, no face-to face classes at schools, when some reflections and difficulties, as well as surprises of how cooperatives can influence, in a positive way, collaborative behaviors in the midst of difficulties in the time we have no exact answers. The analysis of the results demonstrated the impact of the experience on those involved and its influence on the students' individual and collective behavior. The aim of this work is to highlight the importance of school cooperatives in the training of young people as well as the pedagogical possibilities of this proposal in the school context.
Keywords: Cooperativismo; Cooperativa escolar; Educação cooperativista; Cooperativism; School cooperative; Cooperative education